SARS-CoV-2 Proteins Exploit Host’s Genetic and Epigenetic Mediators for the Annexation of Key Host Signaling Pathways - Khan, Md. Abdullah-Al-Kamran; Islam, Abul Bashar Mir Md. Khademul (Frontiers in Molecular Biosciences, 2021)
The constant rise of the death toll and cases of COVID-19 has made this pandemic a serious threat to human civilization. Understanding of host-SARS-CoV-2 interaction in viral pathogenesis is still in its infancy. In this study, we utilized a blend of computational and knowledgebase approaches to model the putative virus-host interplay in host signaling pathways by integrating the experimentally validated host interactome proteins and differentially expressed host genes in SARS-CoV-2 infection. While searching for the pathways in which viral proteins interact with host proteins, we discovered various antiviral immune response pathways such as HIF-1 signaling, autophagy, RIG-I signaling, Toll-like receptor signaling, Fatty acid oxidation/degradation, and IL-17 signaling. All these pathways can be either hijacked or suppressed by the viral proteins, leading to the improved viral survival and life-cycle. Aberration in pathways such as HIF-1 signaling, and Relaxin signaling in lungs suggest the pathogenic lung pathophysiology in COVID-19. From enrichment analysis, it was evident that the deregulated genes in SARS-CoV-2 infection might also be involved in heart development, kidney development, and AGE-RAGE signaling pathway in diabetic complications. Anomalies in these pathways might suggest the increased vulnerability of COVID-19 patients with comorbidities. Moreover, we noticed several presumed infection-induced differentially expressed transcription factors, and epigenetic factors such as miRNAs and several histone modifiers which can modulate different immune signaling pathways, helping both host and virus. Our modelling suggests that SARS-CoV-2 integrates its proteins in different immune signaling pathway and other cellular signaling pathways for developing efficient immune evasion mechanisms, while leading the host to more complicated disease condition. Our findings would help in designing more targeted therapeutic interventions against SARS-CoV-2.